The Natural Antioxidants, Pomegranate Extract and Soy Isoflavones, Favourably Modulate Canine Endothelial Cell Function. (26th November 2012) - Baumgartner-Parzer, Sabina M.; Waldenberger, Ferdinand Rudolf; Freudenthaler, Angelika; Ginouvès-Guerdoux, Amandine; McGahie, David; Gatto, Hugues
Abstract : Cardiovascular disease, preceded by vascular endothelial dysfunction, is a prominent cause of death in dogs. L-carnitine and taurine, well known for their antioxidative capacity, beneficially affect cardiovascular disease as well as certain dog cardiomyopathies. It is well established that vascular endothelial dysfunction precedes cardiovascular disease and that "vasoprotective factors" (NO and antioxidants) prevent apoptosis, whereas "risk factors" such as oxidized LDL, hyperglycemia, and free fatty acids trigger it in cultured human vascular endothelial cells. Whereas human vascular cell in vitro models are widely established and used for the characterisation of potential vasoprotective substances, such models are not available for canine endothelial cells. In the present study we therefore developed an in vitro model, which allows the testing of the effects of different substances on proliferation and apoptosis in canine aortic endothelial cells. This model was used to test L-carnitine, taurine, pomegranate extract, and Soy Isoflavones in comparison to reference substances (glutathione and pioglitazone) previously shown to modulate human endothelial cell function. L-carnitine and taurine neither exhibited antiproliferative nor antiapoptotic activities in the context of this study. However extracts from pomegranate and soy isoflavones dramatically reduced proliferation and apoptosis in a dose dependent fashion, being in line with a vasoprotective activity in dogs.